Undrained Shear Strength from Field Vane Shear Test (VST) of Soil at Shoreline Area - Hamid, Nor Baizura; Mokhtar, Mardiha; Daud, Mohd Effendi; Abd Kadir, Aslila; Kaamin, Masiri; Mohammad Azmi, Mohamad Azim; Sahat, Suhaila; Kamaruddin, Syamsul Azrin; Sabri, Muhamad Syamil; Azlan, Azreen Shafiqa Nabilla (semarak ilmu, 2024)
The effect of soil shear strength at the shoreline area is the focus of this study. Pantai Punggur, Batu Pahat, Johor, has been chosen as the subject location for the soil shear strength investigation. It is located on the west coast of Johor, with latitudes ranging from 1.62° to 1.87° N and longitudes ranging from 102.78° to 103.19° E. The purpose of this study is to use a field vane shear test (VST) to determine the undrained shear strength of shoreline areas. Soil samples were collected at specific locations known as Zones A, B, C, D, and E, and data for sediment shear strength was obtained from field vane shear test (VST) methods. From the undrained shear strength test at 0.5 m depth at high tide (HT) and medium tide (MT) data for December 2021, Zone A had a Cu reading of more than 4.5 kPa, followed by Zones B, C, and D, and lowest at Zone E. Next, in the December 2021 data at the HT level, Zone A has a Cu reading greater than 4.5 kPa at 0.5 m and 1.0 m, while other Zones have readings less than 3.0 kPa. It can be concluded that the depth of a part also influences the data in this study. When the depth increases, the shear strength of the data also increases. This study will serve as a benchmark for future conservation efforts. Based on the findings, more effective control measures for preserving and conserving coastal areas may be developed.